ANALISIS TERHADAP PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN KEUANGAN DESA - Meilany, Sherly; Amin, Muhammad (Limbago: Journal of Constitutional Law, 2023)
Abstract The purpose of this research was to analyzed the concept of regulation of the Minister of home affairs of the Republic of Indonesia number 20 of 2018 concering village financial management, as well as analyzed the legal certainty of implementation the Minister of home affairs of the Republic of Indonesia number 20 of 2018 concering village financial management. This research was normative juridical with Case approach, Statuta approach, Comparative approach and conceptual approach. The result of this research was the concept of regulation of the Minister of home affairs of the Republic of Indonesia number 20 of 2018 concering village financial management was regulate the use and utilization of village finances starting from planning, implementation, administration of reporting and accountability of village finances in a transparent, accountable and participatory mannder.. This is because the norms in Permendagri Number 20 of 2018 are carried out based on the provisions in the applicable laws and regulation, Permendagri Number 20 of 2018 it has also regulated every detail regarding village financial management starting from the implementation, planning and administration stages, Permendagri Number 20 of 2018 has also regulated sanctions for violations of village financial management. Keywords : Permendagri, village, village financial management